Preliminary study for the creation of a test of pragmatics for Chinese students of Spanish as a foreign language - Gibert-Escofet, Isabel; Gutiérrez-Colón Plana, Mar (Onomázein, 2020)
If the studies of pragmatics of the interlanguage are few, there are still fewer that are carried out for the development of the pragmatic competence assessment in foregin/second language through tests that evaluate pragmatics. There is neither a level test to measure the pragmatic understanding of Spanish nor is there a test specific for students who speak Spanish. The objective of this study is to establish the basis on which the foundations of a future pragmatic test for Chinese students who study Spanish as a foreign language will be established. To achieve this purpose, an ethnographic study that starts from the exemplary generation method and serves to detect the degree of difficulty with which the most common situations of a student’s university life are perceived has been carried out. Due to this preliminary study, in which the same students and some native experts provide us with this information, we can say that the items created and analysed meet the quality requirement, which means that the bases of the pragmatic test are correctly established. All these specifications indicate that and the final questionnaire can now be developed.